LEGAL PROTECTION OF PRESS FREEDOM IN THE INTERNATIONAL ARMED CONFLICT IN UKRAINE(Case Study of the Russia-Ukraine War 2014–2022) - Anastasya Rifatia Zahra; Zunnuraeni (Department of Law, Faculty of Law, University of Mataram, 2026)
This research examines the protection of press freedom under international law during the armed conflict in Ukraine from 2014 to 2022, marked by Russia’s annexation of Crimea and subsequent military invasion. The purpose of this study is to analyze legal protection regulations and propose mechanisms for safeguarding press freedom. This research uses a normative juridical approach, utilizing conceptual analysis, international treaties, and case studies. The legal materials used consist of primary, secondary, and tertiary legal sources, analyzed qualitatively through grammatical, systematic, historical, and teleological interpretation methods. The findings show that provisions under International Humanitarian Law, such as the 1949 Geneva Conventions and Additional Protocol I of 1977, primarily focus on the protection of individual journalists as stipulated in Article 79, without extending such protection to press institutions as civilian objects. This normative gap leaves media organizations vulnerable to various violations, both physical and non-physical, including censorship, restrictions on access to information, and attacks on broadcasting infrastructure. Therefore, strengthening and amending international humanitarian law—integrated with international human rights instruments—is necessary to ensure that press freedom as an institution receives comprehensive and effective legal protection during international armed conflicts. This would also preserve the press’s role as a pillar of democracy and a means of public oversight.